(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A simple, sensitive and reproducible UV visible spectrophotometric method has been developed for the quantitative determination of fenofibrate in bulk drug and pharmaceutical dosage forms using MBTH reagent. The method is based on the measurement of absorbance of fenofibrate in methanol (0.5% MBTH in 0.5% HCl and 1% FeCl3 in 0.5% HCl) at 596 nm. Beer’s law is obeyed over the linear range 2-5µg /ml of fenofibrate for the method with apparent molar absorptivity value of 1909.5905 L mol-1cm-1. The method was validated in accordance with the current ICH guidelines. The precision results, expressed by reproducibility (RSD  1.7%) and repeatability (RSD  1.5%), were satisfactory. The accuracy is also satisfactory (RSD  0.200532%). The result demonstrated that the proposed method is accurate, precise and reproducible.